1983
DOI: 10.1002/j.1556-6978.1983.tb01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Education and Supervision: Reader Perceptions

Abstract: This study reports the perceptions of ACES members concerning CES. Demographic characteristics of respondents, opinions on article types, strengths and weaknesses, and inclusion of brief reports and special Issues are presented. Results indicate that research articles are of adequate quality and the types of articles included in the journal are adequate. These and other results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although journal self-citation percentages might imply degree of readership, as suggested by Cotton and Anderson (1973), they may not present a wholly accurate picture. For example, the data presented a fairly strong, although fluctuating, pattern of journal self-citations of CE&S, yet West and Hosie (1983) found that about 85% of those ACES members who responded to their reader survey read 40% or less of each issue of CE&S.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although journal self-citation percentages might imply degree of readership, as suggested by Cotton and Anderson (1973), they may not present a wholly accurate picture. For example, the data presented a fairly strong, although fluctuating, pattern of journal self-citations of CE&S, yet West and Hosie (1983) found that about 85% of those ACES members who responded to their reader survey read 40% or less of each issue of CE&S.…”
Section: Discussionmentioning
confidence: 98%
“…Among their findings was that the percentage of citations of the journal's own articles, or self-citations, rose steadily over the five selected volumes from 2.5% in 1954 to 17% in 1970; that percentages of citations of articles from the Journal of Consulting Psychology and Educational and Psychological Measurement declined; and that percentages from other sources remained relatively stable, although total numbers of citations had increased approximately five-fold. Reader perceptions of P&GJ were studied by Remer and Barclay (1978), and West and Hosie (1983) studied perceptions of CE&S. Both studies examined the "fit" between the articles published by each journal and the perceived needs of the journal's readership. Both studies found the journals to be fairly repre-sentative of their constituencies, both in terms of the types of articles (e.g., application, theory, reaction) and in terms of interests.…”
mentioning
confidence: 99%
“…The articles, however, must be written to facilitate the occurrence of this type of application. This is a current concern of readers of the journal (West & Hosie, 1983). Counselor educators need to adopt this concept of continuation of training when developing articles for the journal.…”
Section: Content Analysismentioning
confidence: 99%